A quantum particle under the action of “white noise” type forces - Gikhman, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We obtain the Schrödinger equation for the wave function of a particle interacting with the external field having a potential containing a component of the “white noise” type and the Kolmogorov equations for the distribution of a wave function.